Mice lacking neutral amino acid transporter B0AT1 (Slc6a19) have elevated levels of FGF21 and GLP-1 and improved glycaemic control - Jiang, Yang; Rose, Adam J.; Sijmonsma, Tjeerd P.; Herzig, Stephan (Molecular metabolism, 2015)
Objective - Type 2 diabetes arises from insulin resistance of peripheral tissues followed by dysfunction of β-cells in the pancreas due to metabolic stress. Both depletion and supplementation of neutral amino acids have been discussed as strategies to improve insulin sensitivity. Here we characterise mice lacking the intestinal and renal neutral amino acid transporter B0AT1 (Slc6a19) as a model to study the consequences of selective depletion of neutral amino acids. - Methods - Metabolic tests, analysis of metabolite levels and signalling pathways were used to characterise mice lacking the intestinal and renal neutral amino acid transporter B0AT1 (Slc6a19). - Results - Reduced uptake of neutral amino acids in the intestine and loss of neutral amino acids in the urine causes an overload of amino acids in the lumen of the intestine and reduced systemic amino acid availability. As a result, higher levels of glucagon-like peptide 1 (GLP-1) are produced by the intestine after a meal, while the liver releases the starvation hormone fibroblast growth factor 21 (FGF21). The combination of these hormones generates a metabolic phenotype that is characterised by efficient removal of glucose, particularly by the heart, reduced adipose tissue mass, browning of subcutaneous white adipose tissue, enhanced production of ketone bodies and reduced hepatic glucose output. - Conclusions - Reduced neutral amino acid availability improves glycaemic control. The epithelial neutral amino acid transporter B0AT1 could be a suitable target to treat type 2 diabetes.
Im Titel ist "0" hochgestellt
Gesehen am 09.06.2020